Influence of moisture content on bending strength of Sapucaia Wood (Lecythis pisionis cambesse) (Research, Society and Development, 2022)
Sapucaia (Lecythis pisionis cambesse) is a species that makes up the botanical family lecythidacea and is commonly found in the Brazilian Amazon, being widely used in heavy internal and heavy external constructions. The objective of this work is to evaluate the influence of the moisture content on the stiffness and flexural strength of sapucaia wood pieces. 18 CPs were used to measure the moisture content using the gravimetric method, with mass measurement at 24-hour intervals and for the bending test, 3 CPs were used per moisture content. With this, it was observed that between 0 and 7 days the measurement of moisture content there was a variation of 13.64% and in the interval between 7 and 14 days there was no significant gain in moisture, with an increase of only 0.61% at the end of the 14 days. In the bending tests, the modulus of rupture (MOR) were obtained, in which the minimum value for 0 days was 94.99 MPa and the maximum value was 118.65 MPa. It was found that the moisture content of the wood, at the time of acquisition, was above the Fiber Saturation Point (29.56%) and its modulus of rupture was 104.36 MPa. In this way, it was possible to verify that the moisture content varied with the submersion time and, as for the average modulus of rupture, it was found that there was no variation.